SUBMICROSCOPIC CHANGES OF THE HEMOCAPILLARIES IN THE ADRENAL GLAND CORTEX IN DYNAMICS AFTER EXPERIMENTAL THERMAL INJURY - Kulbitska, V.V.; Nebesna, Z.M.; Kramar, S.B.; Hetmaniuk, I.B. (World of Medicine and Biology, 2021)
The purpose of the study was to establish submicroscopic changes in the hemocapillaries of the adrenal gland of white rats in the dynamics after experimental thermal injury. The experiment was performed on 36 mature white male rats. Burns of 2B degree were simulated under thiopental-sodium anesthesia. Submicroscopic changes were studied on days 1st, 7th, 14th and 21st from the beginning of the experiment. Small pieces of adrenal cortex were taken for electron microscopic examination. Tissue processing was performed according to generally accepted methods. Ultrathin sections were studied in an electron microscope PEM-125K. In the early period after experimental thermal trauma there are initial destructive changes in the components of the blood capillaries wall of the organ, which were overfilled with blood, there were manifestations of excessive edema, destruction of the cytoplasm in the endothelial cells and pericytes, deformation of nuclei, uneven thickening of the basement membrane. In the late post-burn period, significant destructive-degenerative changes in the wall of hemocapillaries of the adrenal cortex were found. They were accompanied by uneven thickening and homogenization of the basement membrane, pyknosis of nuclei, destruction and fragmentation of organelles in the cytoplasm of endothelial cells, violation of fenestration and disappearance of micropinocytic vesicles, which lead to insufficiency of transendothelial metabolism in the body.